Waqf development in Malaysia - Laldin, Mohamad Akram; Syed Abdul Kader, Sharifah Zubaidah; Djafri, Fares (Routledge, 2021)
This chapter presents a country case study of waqf development in Malaysia. It begins with a brief history of waqf in Malaysia and then explains the governance system where administration of waqf is placed in the hands of each State Islamic Religious Council ('SIRC') of the respective states (13) and federal territories (3, sharing one council). After explaining the legal and administrative framework of waqf, the authors identify several reforms in waqf concept and governance, for example, the development of awqaf lands, the Ahmad Dowjee Dhadaboy waqf project of Menara Imarah by the Federal Territory Islamic Religious Council (MAIWP), waqf hotels projects in Terengganu and Negeri Sembilan, waqf clinics by Waqf Annur Corporation and the Labuan International Waqf Foundation. The chapter then discusses transformation of waqf into various forms such as cash waqf schemes, corporate share waqf, sukuk waqf, takaful waqf model and crowdfunding waqf. The authors then identify some of the challenges for awqaf in Malaysia and conclude with the hope that future changes in government will not interfere with the momentum for reformation and transformation of awqaf in Malaysia.